Serum Ferritin as a Risk Factor for Myocardial Infarction (TAJ: Journal of Teachers Association, 2009)
Myocardial Infarction (Ml) is the most common form of heart disease and the single mostimportant cause of premature death in the developed and developing world. Unfortunately theincidence of the condition is increasing rapidly in many developing countries like Bangladesh.Effort should therefore be taken to minimize the risk factors of Ml. There are several studieswhich evaluate the relation of serum ferritin with Ml in abroad. In Bangladesh, there is no suchstudy was carried out to evaluate the relationship between serum ferritin and Ml. So the presentwork has been designed to evaluate the association of serum ferritin with Ml.The present study was carried out in the Department of Biochemistry, BSMMU in collaborationwith Department of Cardiology, BSMMU and NICVD, Dhaka during the period of July 2001 toDecember 2002. A total of 50 subjects were selected, Group A ( 20 subjects of Ml) and Group B(30 subjects of Control). The mean level of serum ferritin in control subjects were 111.65 ±50.47 ng/ml and in test subjects were 258.44 ± 87.87 ng/ml. So the present study showed thatserum ferritin level is significantly higher in patients with Ml. From the present study, it isdifficult to draw any definite conclusion but suggested that high serum ferritin concentrationmay be a cause of the incidence of Ml.doi: 10.3329/taj.v16i1.3893TAJ June 2003; Vol.16(1): 5-7